DETECTION OF POTENTIALLY PATHOGENIC BACTERIA IN BUTCHER SHOPS: FIRST REPORT FROM AL MANDAQ CITY, SAUDI ARABIA - Melebari, Mohammad (Polish Journal of Natural Sciences, 2023)
Food-borne pathogens cause significant economic losses and affect the quality of life. Of all food products, meat is used most commonly and may be the source of these pathogens. Unfortunately, butcher shops act as a perishable commodity and contribute to the possible spread of food-borne pathogens, toxins, and other contamination. Due to the absence of knowledge and studies related to food safety in Al Mandaq, Saudi Arabia, the main objective of this study was to initiate and establish a database about the possibilities of the existence of pathogenic bacteria in butcher shops in the city. From each shop, 14 samples were collected from various spots, and the bacterial pathogens were identified on specific media. All the strains showed hemolysis except Salmonellae spp., which was non-hemolytic. Based on the number of pathogens, Shop 1 was the most contaminated (n = 57), followed by Shop 2 (n = 51). Among the collected samples, lamb meat contained the highest number (25) of all pathogens, followed by beef, the floor, and the fridge (22 each). The prevalence of S. aureus was 29%, followed by Salmonella spp. (26%) and E. coli (24%) in all the samples of the six butcher shops. All 84 samples were less contaminated with Salmonellae spp. (10%) compared with other isolated pathogens. The increased frequency of these pathogens in meat shows the appallingly unhygienic and unsanitary techniques used, from the slaughterhouse, during transportation to butcher shops, and during processing at the butcher shops. As a result, the current investigation, which is the first of its type in Al Mandaq, demonstrates that meat is highly contaminated with bacterial pathogens. Minimizing meat contamination in markets and using good sanitation and inspection techniques are crucial.